Laser ablation-single-particle-inductively coupled plasma mass spectrometry as a multimodality bioimaging tool in nano-based omics. Issue 3 (19th February 2021) - Metarapi, Dino; van Elteren, Johannes T.; Šala, Martin; Vogel-Mikuš, Katarina; Arčon, Iztok; Šelih, Vid S.; Kolar, Mitja; Hočevar, Samo B.
Abstract : Visualisation of the ionic metal content and the metal nanoparticle number, distribution and size in biomatrices by LA-sp-ICPMS imaging. Abstract : Advanced data processing and visualization techniques were applied to laser ablation-single particle-inductively coupled plasma mass spectrometry (LA-sp-ICPMS) data obtained from imaging of roots of sunflower ( Helianthus annuus L.) which were exposed to ionic silver (Ag + ). Highly multiplexed images with tissue level resolution were generated, showing the uptake and transformation of Ag + to silver nanoparticles (AgNPs) in whole root cross-sections, and revealing that the size of biosynthesized AgNPs is predisposed by the reducing power of particular root compartments. Various Ag + and AgNP visualization strategies are shown with special emphasis on spatially resolved information associated with the number and spherical-equivalent size of individual AgNPs in user-selected root cross-sectional regions, including statistical analysis of the AgNP distribution. Normally, this multimodality information can only be obtained by combining the results of techniques from several complementary platforms.